Deselularisasi Hati sebagai Scaffold Rekonstruksi Organoid Hati - Sibuea, Christine Verawaty (Buletin Farmatera, 2021)
The latest approach in tissue engineering techniques is the use of deselularized native organ as scaffolds for organ reconstruction. Scaffolds made from natural or synthetic matrix have many shortcomings in providing ideal extracellular matrix microstructure for cell proliferation and differentiation. Deselularized native scaffold can maintain the extracellular matrix of native organs, as an ideal microstructure scaffold for cell proliferation and differentiation. This technique answers the challenge of high need for liver transplants due to the limitations of liver donors and the need as liver models for drug testing.for drug testing. Liver is a complex organ, so ideal microstructure is needed in liver organoid reconstruction techniques to produce good synthetic and metabolic functions of the liver